Born rule and Schroedinger equation from first principles. (September 2019) - Oeckl, Robert
Abstract: A concise review of the derivation of the Born rule and Schroedinger equation from first principles is provided. The starting point is a formalization of fundamental notions of measurement and composition, leading to a general framework for physical theories known as the positive formalism. Consecutively adding notions of spacetime, locality, absolute time and causality recovers the well established convex operational framework for classical and quantum theory. Requiring the partially ordered vector space of states to be an anti-lattice one obtains quantum theory in its standard formulation. This includes Born rule and Schroedinger equation.